Modern Railway Engineering - Hessami, Ali (IntechOpen, 2018)
Since the advent of steam engines and higher throughput railways during the early nineteenth century, the rate of development has been rather steady and incremental. The development of advanced electronic control and command systems, increasing levels of automation, and electrified high-speed railways over the past few decades have transformed the rail transportation posing it as a competitor to aviation. Modern railways are no longer the sole forte of civil and mechanical engineering and involve a broad multidisciplinary engineering disciplines from advanced computing, telecommunications, and networking to big data analytics and even AI. This volume addresses the diverse, evolving, and advanced engineering disciplines including enabling practices and processes involved in shaping modern railways.